HUBUNGAN KOMUNIKASI ANTAR PRIBADI GURU DAN SISWA DENGAN MOTIVASI BELAJAR SISWA PADA MATA PELAJARAN AL-QUR’AN HADIST DI MTS MIFTAHUL JANNAH KECAMATAN PERANAP KABUPATEN INHU - Bela Mustika (LEMBAGA PENELITIAN DAN PENGABDIAN MASYARAKAT (LPPM) UNIKS, 2019)
This study aims to find out how and to what extent the relationship of interpersonal communication between teachers and students with student motivation in the subject of the Qur'an Hadith. The research conducted is a quantitative correlational research using quantitative and qualitative approaches. To get the data needed, researchers use observation techniques, interviews, questionnaires and documentation. From this study it can be concluded that the Relationship of Interpersonal Communication Teachers and Students in MTs Miftahul Jannah Peranap District Indragiri Hulu District by 0.019% with the category